THE EFFECT OF EARLY MOBILIZATION ON UTERINE INVOLUTION AFTER CESAREAN SECTION - Femmy Dwi Isminarti; Jasmawati ,; Lukman Nulhakim (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Several factors influence the achievement of Exclusive Breastfeeding, including the presence of mothers experiencing nipple soreness, which consequently leads to discontinuation of breastfeeding; insufficient breast milk flow resulting in a switch to formula milk. One alternative to improve breast milk flow is through the application of Woolwich massage. Woolwich massage therapy is a technique that stimulates breast milk production in nursing mothers. To determine the effect of Woolwich massage on the improvement of breast milk production in postpartum multipara mothers in the postpartum room of Kudungga General Hospital. This study employed a quasi-experimental design, specifically a non-equivalent control group design. The results of this study revealed a significant effect of Woolwich massage on the improvement of breast milk production (p-values of 0.008 and 0.005) with α value of 0.05. The increase in breast milk production can be attributed to the process of milk formation that occurs after stimulation through massage. Contraction of these specialized cells then propels breast milk from the alveoli through the lactiferous ducts to the lactiferous sinuses, where milk is stored. In the first week after childbirth, around 6 out of 10 postpartum mothers commonly experience insufficient breast milk production. Woolwich massage intervention is necessary, with the expectation of enhancing breast milk production in postpartum mothers.